2018
DOI: 10.1177/1129729818801556
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre, randomised, blinded, control trial of drug-eluting balloon vs Sham in recurrent native dialysis fistula stenoses

Abstract: Paclitaxel drug-eluting balloon significantly delays restenosis after angioplasty for recurrent autogenous arteriovenous haemodialysis fistula stenosis, persisting to 12 months. Drug-eluting balloon significantly increases freedom from reintervention at 12 months with these effects true in stented and unstented fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 19 publications
(24 reference statements)
0
75
0
Order By: Relevance
“…After reviewing the titles and abstracts, 999 publications were excluded. After reviewing the full text of 20 publications, 11 publications were included in the final qualitative and quantitative analyses, with a total of 976 patients [8][9][10][11][12][13][14][15][16][17][18]. The flow diagram of the systematic search process is depicted in…”
Section: Study Selectionsmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 999 publications were excluded. After reviewing the full text of 20 publications, 11 publications were included in the final qualitative and quantitative analyses, with a total of 976 patients [8][9][10][11][12][13][14][15][16][17][18]. The flow diagram of the systematic search process is depicted in…”
Section: Study Selectionsmentioning
confidence: 99%
“…It is also the first large multicenter trial to study DCBs in AVFs, and as such builds on the growing literature regarding the use of DCBs in arteriovenous access circuits. Most, but not all, randomized controlled trials to date (all of which are small and most of which are single-center) have shown a benefit for DCB use in AVGs and AVFs (17)(18)(19)(20)(21)(22)(23)30,31). Some trials have used a DCB-first approach, and others an approach similar to that of the present study, namely DCB angioplasty after successful vessel preparation.…”
Section: Discussionmentioning
confidence: 79%
“…Paclitaxel-coated balloon angioplasty has been shown in most, but not all, small randomized trials to yield superior patency compared with standard PTA in hemodialysis circuits (17)(18)(19)(20)(21)(22)(23). The present large multicenter randomized study was designed to test the hypothesis that drug-coated balloon (DCB) angioplasty performed after successful vessel preparation with high-pressure PTA would yield superior outcomes.…”
mentioning
confidence: 99%
“…To date, multiple observational and randomized controlled studies have evaluated the use of DCBs for prolonging patency, but caution should be taken when interpreting the results due to clinical heterogeneity resulting from the non-uniform level of intervention ( 8 9 11 12 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ). In a retrospective study in 2014, Patanè et al ( 9 ) presented a case series of 26 patients who had juxta-anastomotic radiocephalic stenosis treated using DBA.…”
Section: Discussionmentioning
confidence: 99%